2014
DOI: 10.1155/2014/616240
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Correlation of the Morphology of Coiled Carbon Nanotubes with Their Response to Axial Compression

Abstract: The mechanical response of thirteen different helical multi-walled carbon nanocoils to axial compression is reported. Each nanocoil was attached to the apex of a cantilever probe tip; its dimensions and orientation relative to the tip apex were determined with scanning electron microscopy. The atomic force microscope was employed to apply a cyclic axial load on the nanocoil. Its mechanical response was determined by simultaneous collection of the thermal resonance frequency, displacement, and oscillation ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…In their results, average CCNT spring constant and tensile strength were evaluated around 1.8 N/m and 100 MPa, respectively. By using the multidimensional force spectroscopy technique, Barber et al 44 demonstrated unique signatures for buckling, bending, and slip-stick events of the nanocoil under compression. Moreover, the elastic moduli of 13 CCNTs were calculated ranging from 0.4 to 31.4 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…In their results, average CCNT spring constant and tensile strength were evaluated around 1.8 N/m and 100 MPa, respectively. By using the multidimensional force spectroscopy technique, Barber et al 44 demonstrated unique signatures for buckling, bending, and slip-stick events of the nanocoil under compression. Moreover, the elastic moduli of 13 CCNTs were calculated ranging from 0.4 to 31.4 GPa.…”
Section: Introductionmentioning
confidence: 99%